Translation and survival the Greek Bible and the Jewish Diaspora - Rajak, Tessa 1946- (Oxford Oxford University Press, 2009)
A study of the translation of the Hebrew Bible into Greek - a work of seminal importance, without which there would have been no Western Jewish disapora, and no Christianity. The book places its production in historical context, and examines its role in the religious culture of Jews in the Mediterranean during this period.
Electronic reproduction.
Keywords: Bible -- Translations into Ancient Greek; Jews -- History -- To 70 A.D. -- Mediterranean Region; Jews -- Civilization -- Greek influences; Electronic books